Meta-Heuristic Development in Combinatorial Optimization. (August 2019) - Iqbal, Muhammad; Zarlis, Muhammad; Tulus,; Mawengkang, Herman
Abstract: The quadratic assigment problem is a combinatorial problem of deciding the placement of facilities in specified locations in such a way as to minimize a nonconvex objective function expressed in terms of distance between location and flows between facilities. Due to the non-convexity nature of the problem, therefore to get a 'good' starting point is necessary in order to obtain a better optimal solution. In this paper we propose a meta heuristic strategy combined with feasible neighbourhood search to get 'optimal' solution. From computational experience in solving some backboard wiring problems, it turns out that the approach proposed is promising.